Adsorption of Dye on Peanut Shell-Based Activated Carbon: A Review Article - Stephen Samuel; Abdulkarim Haruna Aliyu; Amos Musa Stone; Amina Ali; Tukur Rilwan (International Journal of Education, Management, and Technology, 2026)
Agricultural by-products such as peanut shells provide a renewable alternative to coal-based activated carbon by combining wastewater-treatment potential with agricultural waste valorization. This review examines the performance of peanut shell-based activated carbon (PSAC) in dye adsorption and evaluates the kinetic, equilibrium, and mechanistic models used to describe dye-removal processes. The review synthesizes reported evidence concerning adsorption kinetics, including pseudo-first-order and pseudo-second-order models, and adsorption isotherms, particularly the Langmuir and Freundlich models. The findings demonstrate that PSAC exhibits a high adsorption capacity for dyes such as methylene blue and crystal violet, with adsorption predominantly characterized by chemisorption and monolayer surface interactions. These findings indicate that PSAC is an effective and economical biomass-derived adsorbent for removing dyes from wastewater while supporting the beneficial reuse of agricultural residues. The review contributes an integrated understanding of PSAC adsorption performance and the models used to explain its dye-removal mechanisms. Further research should prioritize improving adsorbent regeneration, developing advanced PSAC-based composite materials, and scaling up adsorption systems for industrial wastewater-treatment applications.